2023
DOI: 10.1371/journal.pmed.1004169
|View full text |Cite
|
Sign up to set email alerts
|

Demand creation for HIV testing services: A systematic review and meta-analysis

Abstract: Background HIV testing services (HTS) are the first steps in reaching the UNAIDS 95-95-95 goals to achieve and maintain low HIV incidence. Evaluating the effectiveness of different demand creation interventions to increase uptake of efficient and effective HTS is useful to prioritize limited programmatic resources. This review was undertaken to inform World Health Organization (WHO) 2019 HIV testing guidelines and assessed the research question, “Which demand creation strategies are effective for enhancing upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 141 publications
0
4
0
Order By: Relevance
“…While previous studies have confirmed that financial incentives may increase HIV testing uptake in the short‐term, in general, cash‐based incentives did not seem to consistently improve linkage to care or ART initiation [56, 57, 94]. While they were appreciated by participants, they elicited ethical discussions on who can be influenced by money and what can be bought if other alternatives to access healthcare were available, for example borrowing money for transport or walking to healthcare facilities [87].…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have confirmed that financial incentives may increase HIV testing uptake in the short‐term, in general, cash‐based incentives did not seem to consistently improve linkage to care or ART initiation [56, 57, 94]. While they were appreciated by participants, they elicited ethical discussions on who can be influenced by money and what can be bought if other alternatives to access healthcare were available, for example borrowing money for transport or walking to healthcare facilities [87].…”
Section: Discussionmentioning
confidence: 99%
“…It is critical to identify the optimal delivery models of caregiver‐targeted education in sub‐Saharan Africa, which may be adapted for varied regional settings. Video‐based interventions are efficient for reducing healthcare worker burden; in clinics with technological capabilities, educational videos for mothers in waiting rooms could improve child neurodevelopmental outcomes [ 129 , 130 , 131 , 132 ]. There is also a need to reach caregivers who are not engaged in clinical care, through non‐clinic, community‐based or home‐delivered interventions that leverage community health workers and mobile health innovations [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…Virtual interventions are now recommended by the World Health Organization (WHO) to reach KPs with HIV testing [5–7]. Platforms in many countries have integrated HIV self‐testing (HIVST) models into a digital or web‐assisted service—with various formats of digital service model increasing testing uptake and coverage compared to facility‐only models.…”
Section: Introductionmentioning
confidence: 99%